Baby gap: Does more education make for less children? - Matthias Westphal; Daniel A. Kamhöfer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
Female college graduates are less likely to bear children but once a mother, they have more children than non-college graduates. - RWI presents first evidence on why college educated women have less children than women who did not go to college. While tertiary education has a direct negative impact on women's probability to become a mother, college educated mothers bear more children than noncollege educated mothers. Career disadvantages might discourage highly educated women from having children. More flexible working hours and means-tested maternal leave benefits could reduce the baby gap.
Keywords: 330